2011
DOI: 10.1016/j.exer.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor activation modulates antimicrobial peptide expression by ocular surface cells

Abstract: The ability of the ocular surface to respond to pathogens is in part attributed to toll-like receptors (TLRs) that recognize conserved motifs on various microbes. This study examines TLR expression on various ocular surface cells, if TLR agonists can modulate the expression of antimicrobial peptides (AMPs), human beta defensins (hBD) and cathelicidin (hCAP-18/LL-37) which maybe functionally active against Pseudomonas aeruginosa (PA) and if TLR agonists or AMPs can modulate TLR mRNA expression. TLR1-10 mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 74 publications
4
70
1
1
Order By: Relevance
“…Candidate ExsA-independent factors driving epithelial traversal include various virulence factors shown to be involved in passaging through cultured cells, such as proteases, rhamnolipids, exotoxin A, and the MexAB/OprM antimicrobial efflux pump (27,38,39,41,61). Whatever the case, ExsA-independent factors driving traversal could differ in the 6-h healing corneas and MyD88-compromised corneas considering that (i) the barrier function with regard to fluorescein is lost in the former (45) but not in the latter (47) situation and (ii) that MyD88-deficient epithelia are defective in expression of many defense factors (51,52,62,63), including those identified in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate ExsA-independent factors driving epithelial traversal include various virulence factors shown to be involved in passaging through cultured cells, such as proteases, rhamnolipids, exotoxin A, and the MexAB/OprM antimicrobial efflux pump (27,38,39,41,61). Whatever the case, ExsA-independent factors driving traversal could differ in the 6-h healing corneas and MyD88-compromised corneas considering that (i) the barrier function with regard to fluorescein is lost in the former (45) but not in the latter (47) situation and (ii) that MyD88-deficient epithelia are defective in expression of many defense factors (51,52,62,63), including those identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When blotting was followed by 1 h of EGTA treatment (100 mM in phosphate-buffered saline [PBS]), the bacteria could traverse the epithelium all the way to the underlying basal lamina (46). Using gene knockout mice, we have found that MyD88 is important for protecting the corneal epithelium against both adhesion and subsequent traversal (47) and that mBD3, the mouse equivalent of human hBD2 and a MyD88-dependent factor (51,52), is involved in this protective effect (49). We further showed that these novel methods for studying traversal of in situ-grown corneal epithelium could be adapted for ex vivo use, which allows exclusion of tear fluid and infiltrating phagocytic responses when desirable.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] In addition, bathing tear fluid contains mucins, secretory immunoglobulin A (sIgA), and surfactant protein D, all antimicrobial factors that can bind microbes and potentially alter their interactions with corneal epithelial cells. [13][14][15] Epithelial cells also express several antimicrobial peptides, including human β-defensin 2 (hBD-2), cathelicidin LL-37, 11,12,16,17 and cytokeratin 6A. 18 In addition, superficial epithelial cells can internalise bacteria and then desquamate, thereby reducing the infective load.…”
Section: Corneal Barriers Against Infectionmentioning
confidence: 99%
“…tuberculosis and M. bovis BCG infections modulate TLR and cytokine expression in BM-MSCs. Previous studies have shown that bacterial challenge increases the expression levels of TLRs, which subsequently increase the production of AMPs to reduce the risk of microbial infections (23). It has been shown that cathelicidin expression is regulated mainly via TLR2 and TLR4 signaling cascades (24,25).…”
mentioning
confidence: 99%